Effects of intramuscular fat on the flavor of fresh sheep and goat meat: Recent insights into pre-mortem and post-mortem factors - Tianyu Su; Yu Fu; Jingjie Tan; Mohammed Gagaoua; Kathrine H. Bak; Olugbenga P. Soladoye; Zhongquan Zhao; Yongju Zhao; Wei Wu (Food Chemistry: X)
Sheep and goat meat products are becoming increasingly popular among consumers due to their unique flavor derived from intramuscular fat (IMF), which contributes to formation of the distinctive odor. However, there is currently a dearth of reviews on the impact of IMF on the flavor of sheep and goat meat. The present review aims to discuss the relationships between IMF and flavor through lipid composition and fatty acid (FA) distribution, provide an overview of characteristic flavor compounds affecting the flavor of sheep and goat meat, and shed light on the impacts of pre-mortem and post-mortem factors on meat flavor attributed to changes in FAs and flavor compounds. Controlling pre-mortem practices and adjusting post-mortem harvesting methods are key factors in shaping and/or driving the flavor of sheep and goat meat products. This review enhances the comprehensive understanding of the impact of IMF on the flavor of sheep and goat meat.